Pengaruh Dukungan Teman Sebaya Terhadap Career Decision Self-Efficacy pada Mahasiswa Tingkat Akhir Universitas Kristen Satya Wacana - Alvin Kurniawan; Sri Aryanti Kristianingsih (Riviera Publishing, 2026)
Final-year university students are in a critical transition phase from education to the world of work, which requires the ability to make appropriate career decisions. One factor that is believed to influence individuals’ confidence in making career decisions is peer support. This study aimed to examine the effect of peer support on career decision self-efficacy (CDSE) among final-year university students.This study employed a quantitative approach with an corelational research design. The participants consisted of 52 final-year students at Satya Wacana Christian University, selected using an accidental sampling technique. Data were collected using the Career Decision Self-Efficacy Scale and the Peer Support Scale. Data analysis was conducted using Pearson Product-Moment correlation.The results showed a positive and significant relationship between peer support and career decision self-efficacy among final-year students (r = 0.701; p < 0.01). These findings indicate that higher levels of peer support are associated with higher levels of confidence in making career decisions.Based on these results, it can be concluded that peer support plays an important role in enhancing career decision self-efficacy among final-year students. This study is expected to contribute theoretically to the field of career psychology and practically to the development of peer-based career guidance programs.